30-year changes in Australian children's standing broad jump: 1985–2015. Issue 10 (October 2018) - Hardy, Louise L.; Merom, Dafna; Thomas, Margaret; Peralta, Louisa
Abstract: Objectives: Muscular strength is an important component of fitness that enables the execution of a range of daily activities across the lifespan including sport participation. The purpose of this study was to examine changes in children's standing broad jump, an indicator of muscular strength, between 1985 and 2015. Design: Two representative cross-sectional population surveys of Australian children age 9–15 years (n = 7051). Methods: In 1985 and 2015 children's standing broad jump (SBJ; cm) and anthropometry were measured by trained field teams. General linear regression examined the temporal change in SBJ by sex and age adjusting for height, weight, socioeconomic status, and linguistic background. Results: Over a 30-year period, the height, weight, and BMI of children significantly increased and muscular strength decreased. Among boys, the adjusted SBJ distance declined −4.5 cms (95%CI −8.8, −0.10) in 9–11 year olds and 7.6 cms (95%CI −12.5, −2.7) in 12–15 year olds. Among girls, the adjusted SBJ distance declined 8.5 cms (95%CI −12.9, −4.2) in 9–11 year olds and 9.3 cms (95%CI −14.1, −4.6) in 12–15 year olds. Larger declines in the distance jumped were observed among children and adolescents from non-English speaking backgrounds, than English speaking peers and children from low socioeconomic neighbourhoods than the declines among children from high SES neighbourhoods. Conclusions: Overall, the distance children and adolescents jumped in 2015 was lower than the distance their peers jumped in 1985. The declines differed by sex and sociodemographic characteristics, which suggests targeted sub-population interventions to improve children's muscular strength should be considered.